Distress-reducing strategies for enhancing students' ability to cope with psychological challenges associated with online learning - Camellia, Vita; Khairunnisa, Khairunnisa; Dhiba, Farah; Zulfendri; Khaddafi, Muhammad Rio; Dalimunthe, Heni Indrawati (Universitas Gadjah Mada, 2024)
Purpose: This workshop aims to enhance students' comprehension of online learning and psychological stress. Additionally, it seeks to expand students' awareness of anxiety and depression symptoms and enable them to overcome these conditions by routinely practicing stress-reducing strategies. Methods: Distress-reducing strategies training was conducted at the Health Institute of Sehat Medan from June to September 2021. The training included a focus group discussion and a preliminary survey distributed among female students through Google Forms. The survey collected demographic data, and online learning feedback, and used the Kessler Psychological Distress (K-10) questionnaire to assess the participants' psychological distress levels. Students also learned techniques to help reduce distress. Results: Of the 51 female students who are currently in semesters 2 to 5 participating in the survey, 70.59% admitted to experiencing signal disturbances, 56.9% complained that the lecturers' assignments were burdensome, and 83.4% of them had insufficient resources to buy internet packages. After one year of online learning, students still prefer the offline aspect. It was also discovered that 11.8% of the respondents experienced psychological disorders, while 88.2% of them did not experience distress. Conclusion: Finally, the students found the workshop helpful in reducing their distress and were satisfied with the training.